TLE3,a transcriptional co-repressor, is dispensable for spermatogenesis and male fertility in mice - Yifan Zhao; Haoran Xu; Shumin Zhou; Ziqi Yu; Dalin Liu; Hao Zhou; Shengwei Ke; Fei Sun (Theriogenology, 2026)

Cryogenic ultrasound-assisted ethyl acetate extraction enables selective defatting of egg yolk powder with enhanced phospholipid retention and functionality - Shumin Chen; Xiaoyun Liu; Mohamed Salama; Xiaomeng Li; Lingzhuo Li; Haoyang Sun; Lin Deng; Pengfei Geng; Zehao Wu; Wei Wu; Zhaoxia Cai (Food Research International, 2026)

Microbial and enzymatic synergy in process-intensified ensiling: A biorefinery strategy for corn stover valorization toward lactic acid and bioethanol - Jinge Deng; Shumin Cheng; Guofang Chen; Jiajin Sun; Xueyan Bao; Guangwen Zhang; Gang Guo; Wenjie Huo; Lei Chen (Biomass and Bioenergy, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Role of galloyl moiety in modulating the interaction between Cyperus esculentus protein and tea polyphenols: A structure-activity relationship - Liping Qin; Shumin Yu; Puying Chen; Luoqing Ding; Chunming Zou; Xi Yang; Xuebo Liu; Lijun Sun (Food Chemistry, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Infant-derived bifidobacterium can enhance the ability to respond to influenza virus infection by promoting type I interferon-mediated immunity - Jiaqian Shentu; Qinggang Xie; Minghui Yan; Shumin Wang; Xiaoxuan Sun; Chengcheng Zhang; Peijun Tian; Xiaomei Lv; Bo Yang; Wenwei Lu; Shumao Cui; Gang Wang; et al. (Food Bioscience, 2026)

Effects of Antioxidant DI-3-N-Butylphthalide on Hemorrhagic Transformation Assessed by Propensity Score Matching in a Real-World Thrombolyzed Ischemic Stroke Patient Setting - Ziqi Han; He Liang; Tieping Fan; Mario Minor Murakami Junior; Shumin Li; Ruikang Sun; Daoyong Peng; Shiwei Du; Yu Hasegawa; Haojie Gao; Dong Chen; Dirk M. Hermann; et al. (Translational Stroke Research, 2026)

β-Sitosterol: a Common Compound in Hundreds of Traditional Chinese Medicine Treatments for Infertility and its Effects on Human Ovarian Granulosa Cells - Yu Sun; Gengchen Feng; Ziyi Yang; Yimeng Li; Shumin Li; Shigang Zhao (Phenomics, 2026)

Modeling periodic transcriptions in tandem gene systems - Wangyang Wu; Shumin Tan; Moxun Tang; Qiwen Sun (Mathematical Biosciences, 2026)

Integrating probabilistic modeling and geospatial analysis for nationwide assessment of dietary perchlorate exposure in China: Regional disparities, source contribution, and risk implications - Wenbing Huang; Fu Gao; Yuan Zhong; Gaowei Sun; Kaicheng Liu; Chunsheng Qiu; Yubin Liu; Shumin Xiao (Environmental Pollution, 2026)

Mechanisms of flavonoid-mediated amelioration of MASLD: flavonoids, their metabolites or impact on gut microbes? - Ruxuan Chen; Xionghui Wu; Ning Yin; Enjun Xie; Shumin Sun; Jie Shen; Yunmei Chen; Fenghua Zhou; Tao Li; Qili Li; Donglin Su; Fuhua Fu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Effective degradation of aflatoxin B1 and zearalenone by a recombinant laccase from Heyndrickxia shackletonii - Fred Mwabulili; Peng Li; Qian Li; Shumin Sun; Yuhui Yang; Weibin Ma; Xiao Li; Hang Jia; Yanli Xie (World Journal of Microbiology and Biotechnology, 2026)

Emerging cancer electrotherapeutic technologies: a biomedical engineering paradigm - Yichi Cai; Shumin Sun; Jihu Nie; Nailin Yang; Liang Cheng (Science Bulletin, 2026)

Tracing the geographical origin of tiger nut (Cyperus esculentus L) in China based on stable isotopes and mineral elements combined with multi-modal recognition - Sun Shumin; Wang Nanxi; Sun Tiantian; Luo Xiaohong; Yang Yongtan (Food Chemistry, 2026)

Tuning surface residual lithium into a Li-ion-conductive protective interphase toward stable Ni-rich cathodes - Shumin Liu; Huangzhang Zhou; Wenhao Jia; Yingjie Sun; Peng Gao; Ruichen Zhu; Yongming Zhu; Xudong Li; Liguang Wang (Chemical Engineering Journal, 2026)

Selective lithium recovery from lithium carbonate mother liquor: A combined approach of phosphate precipitation and sulfate roasting - Xiaotian Zhang; Shumin Wu; Shuo Zhang; Daokang Lan; Jing Sun; Zhongwei Zhao; Guoxing Ren; Wenhua Xu; Dongfu Liu (Journal of Water Process Engineering, 2026)

Resistant dextrin/xanthan gum gels protect probiotics for application to ionizing radiation shielding - Minting Wang; Rui Sun; Liuchan Zeng; Shumin Du; Yubao Fang; Bo Zhuang; Bochuan Yuan; Yiguang Jin (Food Research International, 2026)

Lithological predominance in landslide distribution in western Sichuan (China), revealed by multi-sensor remote sensing analysis - Xianlin Shi; Tao Yin; Keren Dai; Wei Sun; Mahdi Motagh; Chen Liu; Shumin Feng; Qiang Xu (Advances in Space Research, 2026)

Taxonomic profiling of maternal and infant-derived Bifidobacterium strains based on in vitro experiments and genomic analysis - Shumin Wang; Chengdong Zheng; Jiaqian Shentu; Shilong Jiang; Qingsong Zhang; Leilei Yu; Wei Chen; Jianguo Sun; Qinggang Xie; Qixiao Zhai (Food Bioscience, 2025)

WDGBANDTI: A Deep Graph Convolutional Network-Based Bilinear Attention Network for Drug-Target Interaction Prediction with Domain Adaptation - Nianrui Wang; Shumin Zhao; Ziwei Li; Jianqiang Sun; Ming Yi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Effects of a dietary liquid extract of Lentinus edodes on the growth performance, immune traits, and intestinal flora of weaned Simmental calves - Mengqi Wang; Yi Yang; Jing Yang; Junlong Bi; Yongjun Zhao; Sirui Wang; Haixia Guo; Shumin Sun (Animal Feed Science and Technology, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

Porous manganese-based ion sieve for sustainable lithium extraction from brine: High-efficiency adsorption and rapid kinetics - Yu Dai; Xiaotian Zhang; Jing Sun; Shumin Wu; Zhongwei Zhao; Wenhua Xu; Guoxing Ren; Yongli Li; Dongfu Liu (Desalination, 2025)

Trps1 targets Scarb1 to regulate cholesterol acquisition in mouse Leydig cells - Xiuli Lian; Zihang Lin; Weitao Hu; Zhangting Chen; Shanshan Luo; Shumin Liao; Yue Liu; Shie Wang; Jiandong Sun (Reproductive Biology, 2025)

Pesticide exposure induces risks of gestational anemia by maternal gut microbiota: A prospective cohort study - Chao Dong; Shumin Yu; Siting Deng; Ziye Xia; Flores Carpintero Rigoberto; Mazhar Sultan; Xiaoyu Xu; Bowen Jin; Quanquan Guan; Zhibin Sun; Yankai Xia (Journal of Hazardous Materials, 2025)

Germline-specific deletion of testis-highly expressed Lrwd1 reveals nonessential roles in male fertility - Chunhai Luo; Dalin Liu; Ziqi Yu; Zhiwei Fan; Haoran Xu; Shumin Zhou; Xuanjing Zhu; Hanchao Liu; Lifu Shao; Yunhao Wu; Zhean Li; Fei Sun; et al. (Theriogenology, 2025)

Role of sn-2 palmitate on the development of the infant gut microbiome: A metagenomic insight - Shumin Wang; Chengdong Zheng; Chaozhi Bu; Danying Guo; Chengcheng Zhang; Qinggang Xie; Jiancun Pan; Jianguo Sun; Wei Chen; Shilong Jiang; Qixiao Zhai (Food Research International, 2025)

Improvement of finescale parameterization through reducing uncertainty in spectrum estimation - Shumin Jiang; Dejun Dai; Dingqi Wang; Jia Deng; Jia Sun; Ying Li; Jingsong Guo; Fangli Qiao (Dynamics of Atmospheres and Oceans, 2025)

Degradation of patulin in aqueous solution and apple juice by titanium dioxide/graphitic carbon nitride: efficiency, quality and safety - Shumin Sun; Mengdan Ku; Jiayi Yang; Wenhao Zhang; Yanli Xie (Food Additives & Contaminants: Part A, 2025)

Biodegradable ionic nanoregulators for synchronous modulation of copper and iron ion homeostasis in breast cancer therapy - Panpan Xue; Huilan Zhuang; Sijie Shao; Hai Cai; Shumin Tang; Ying Sun; Xuemei Zeng; Shuangqian Yan (Chemical Engineering Journal, 2025)

Degradation of AFB1 in edible oil by aptamer-modified TiO2 composite photocatalytic materials: Selective efficiency, degradation mechanism and toxicity - Mengdan Ku; Jiajun Li; Wenhao Zhang; Shumin Sun; Yaqi Zhang; Yanli Xie (Food Chemistry, 2025)

Correlation between pollen morphology, karyotype, floral pigments, and scent components and morphological classification of 15 species and hybrids of Syringa L - Feng Qian; Xiaoou Zhai; Ziyin Cheng; Zhenyu Yu; Guoqiang Chen; Yan Gao; Liwei Sun; Li Fang; Shumin Yang; Shaoqi Xu; Huimin Liu (The Science of Nature, 2025)

The Paraventricular Hypothalamus: A Sorting Center for Visceral and Somatic Pain - Li Sun; Shumin Duan (Neuroscience Bulletin, 2025)

Dongting Lake algal bloom forecasting: Robustness and accuracy analysis of deep learning models - Yuxin Liu; Bin Yang; Kunting Xie; Julong Sun; Shumin Zhu (Journal of Hazardous Materials, 2025)

Effect of Resveratrol on the intestinal microbiota in Type2 diabetes Mellitus mice - Hao Liu; Shumin Wang; Xin Yu; Shuguang Sun; Yingzhen Su (Brazilian Journal of Microbiology, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

An electrically activable nanochip to intensify gas-ionic-immunotherapy - Gang Wang; Jingrui Li; Shumin Sun; Yuqi Yang; Zhihui Han; Zifan Pei; Liang Cheng (Science Bulletin, 2025)

Expression, characterization, and application of an aldo-keto reductase mined from Bacillus velezensis Vel-HNGD-F2 for deoxynivalenol biodegradation - Junxia Liu; Peng Li; Xiao Li; Yanli Xie; Fred Mwabulili; Shumin Sun; Yuhui Yang; Weibin Ma; Qian Li; Hang Jia (Food and Chemical Toxicology, 2025)

Research diversity and advances in simultaneous removal of multi-mycotoxin - Fred Mwabulili; Peng Li; Jinghao Shi; Hongxin Zhang; Yanli Xie; Weibin Ma; Shumin Sun; Yuhui Yang; Qian Li; Xiao Li; Hang Jia (Toxicon, 2024)

Leak detection in water supply pipeline with small-size leakage using deep learning networks - Pengcheng Guo; Shumin Zheng; Jianguo Yan; Yan Xu; Jiang Li; Jinyang Ma; Shuaihui Sun (Process Safety and Environmental Protection, 2024)

A Novel Dual-Scale Equivalent Model for Analyzing the Frequency Response of Wave Propagation in Jointed Rock Mass - Shumin Wang; Zhiliang Wang; Jianguo Wang; Pan Sun (Rock Mechanics and Rock Engineering, 2024)

Identification of microbiological genomes carrying antibiotic resistance genes and virulence factor genes for microbiological risk assessment in filter backwash water - Yongjie Huang; Xiaoyao Weng; Xinlu Qu; Tianxiao Sun; Weiwei Zhang; Shumin Yang; Xin He; Yuan Xiao; Tianyang Zhang; Yulin Tang (Journal of Environmental Chemical Engineering, 2024)

Enhancing Lactobacillus plantarum delivery: Impact of gluconolactone concentration on high-internal-phase emulsion gels and gastrointestinal viability - Chenyuan Sun; Shengnan Wang; Yan Xu; Shumin Wang; Dayu Zhou; He Liu (Food Chemistry, 2024)

Morphological Tracing and Functional Identification of Monosynaptic Connections in the Brain: A Comprehensive Guide - Yuanyuan Li; Yuanyuan Fang; Kaiyuan Li; Hongbin Yang; Shumin Duan; Li Sun (Neuroscience Bulletin, 2024)
Behavioral studies play a crucial role in unraveling the mechanisms underlying brain function. Recent advances in optogenetics, neuronal typing and labeling, and circuit tracing have facilitated the dissection of the neural circuitry involved in various important behaviors. The identification of monosynaptic connections, both upstream and downstream of specific neurons, serves as the foundation for understanding complex neural circuits and studying behavioral mechanisms. However, the practical implementation and mechanistic understanding of monosynaptic connection tracing techniques and functional identification remain challenging, particularly for inexperienced researchers. Improper application of these methods and misinterpretation of results can impede experimental progress and lead to erroneous conclusions. In this paper, we present a comprehensive description of the principles, specific operational details, and key steps involved in tracing anterograde and retrograde monosynaptic connections. We outline the process of functionally identifying monosynaptic connections through the integration of optogenetics and electrophysiological techniques, providing practical guidance for researchers.

Characterization of high-internal-phase emulsions based on soy protein isolate with varying concentrations of soy hull polysaccharide and their capabilities for probiotic delivery: In vivo and in vitro release and thermal stability - Chenyuan Sun; Shengnan Wang; Shumin Wang; Peng Wang; Guangchen Zhang; He Liu; Danshi Zhu (Food Research International, 2024)

Mechanism of inactivation of Aspergillus flavus spores by dielectric barrier discharge plasma - Yaxin Wang; Mingming Yu; Yanli Xie; Weibin Ma; Shumin Sun; Qian Li; Yuhui Yang; Xiao Li; Hang Jia; Renyong Zhao (Toxicon, 2024)

Atomic ruthenium doping in collaboration with oxygen vacancy engineering boosts the hydrogen evolution reaction by optimizing H absorption - Dong Sui; Ruishen Luo; Shumin Xie; Heng Zhang; Tiantian Ma; Hao Sun; Tong-Tong Jia; Jing Sun; Xingyun Li (Chemical Engineering Journal, 2024)

A differential strategy to enhance the anti-interference ability of molecularly imprinted electrochemiluminescence sensor with a semi-logarithmic calibration curve - Shumin Yu; Jiangru Wang; Yue Sun; Qingqing Wang; Qi Kang; Dazhong Shen (Analytica Chimica Acta, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

High mechanical flexible and recyclable organic-inorganic hybrid polyhexahydrotriazine aerogel for oil/water separation - Yi Xu; Keqi Zhu; Xinyue Sun; Shumin Xu; Changhui Liu; Shenghua Xiong; Qichao Ran (Process Safety and Environmental Protection, 2023)

Porous Graphitic phase carbon nitride/graphene oxide hydrogel microspheres for efficient and recyclable degradation of aflatoxin B1 in peanut oil - Shumin Sun; Jiayi Yang; Yajie Liu; Yanli Xie; Fred Mwabulili (Food Chemistry, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Mixing-layer depth-based backwards trajectory analysis of the sources of high O3 concentrations at the Wutaishan station, North China - Shiming Yan; Xingai Gao; Kunning Pei; Hongping Sun; Yan Wang; Fengsheng Zhang; Ying Li; Shumin Wang; Ling Chen; Jian Dong; Feihong Yang (Atmospheric Pollution Research, 2023)

Distribution Characteristics of Nutritional Elements and Combined Health Risk of Heavy Metals in Medicinal Tea from Genuine Producing Area of China - Ming Sui; Dandan Kong; Haonan Ruan; Xinqi Sun; Wei Gu; Mengyue Guo; Shumin Ding; Meihua Yang (Biological Trace Element Research, 2023)

Research progress of ochratoxin a bio-detoxification - Fred Mwabulili; Yanli Xie; Qian Li; Shumin Sun; Yuhui Yang; Weibin Ma (Toxicon, 2023)

Promoting carrier collection by DMF/DMSO binary solvent for efficient kesterite solar cells - Yali Sun; Shumin Qin; Dongliang Ding; Haifeng Gao; Qing Zhou; Xuanyang Guo; Chao Gao; Haixu Liu; Yi Zhang; Wei Yu (Chemical Engineering Journal, 2023)

cFos-ANAB: A cFos-based Web Tool for Exploring Activated Neurons and Associated Behaviors - Fan Wang; Wenjie Sun; Lei Chang; Kefang Sun; Leying Hou; Linna Qian; Chaoyin Jin; Jiandong Chen; Jiali Pu; Panmeng Ye; Shuang Qiu; Jianhong Luo; et al. (Neuroscience Bulletin, 2021)

Interference of anthocyanin extracted from black soybean coats on aflatoxin B 1 -human serum albumin in the binding process - Tingting Fan; Yanli Xie; Shumin Sun (Food Additives & Contaminants: Part A, 2021)

Targeted drug delivery strategies for the treatment of rheumatoid arthritis - Jinxia Zhang; Ling Jiang; Lihong Sun; Ping Wang; Suhui Sun; Menghong Xu; Lulu Zhang; Shumin Wang; Xiaolong Liang; Ligang Cui (Science China Life Sciences, 2021)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

Standardized Operational Protocol for Human Brain Banking in China - Wenying Qiu; Hanlin Zhang; Aimin Bao; Keqing Zhu; Yue Huang; Xiaoxin Yan; Jing Zhang; Chunjiu Zhong; Yong Shen; Jiangning Zhou; Xiaoying Zheng; Liwei Zhang; et al. (Neuroscience Bulletin, 2019)

Dietary Supplementation with Chromium Picolinate Influences Serum Glucose and Immune Response of Brown-Egg Laying Hens - Shumin Zhang; Xiaoming Sun; Xiudong Liao; Lin Lu; Liyang Zhang; Qiugang Ma; Xugang Luo (Biological Trace Element Research, 2018)

EGCG protects against homocysteine-induced human umbilical vein endothelial cells apoptosis by modulating mitochondrial-dependent apoptotic signaling and PI3K/Akt/eNOS signaling pathways - Shumin Liu; Zhengwu Sun; Peng Chu; Hailong Li; Anil Ahsan; Ziru Zhou; Zonghui Zhang; Bin Sun; Jingjun Wu; Yalin Xi; Guozhu Han; Yuan Lin; et al. (Apoptosis, 2017)

Effects of pH and substrate concentrations on dark fermentative biohydrogen production from xylose by extreme thermophilic mixed culture - Chunsheng Qiu; Puyu Shi; Shumin Xiao; Liping Sun (World Journal of Microbiology and Biotechnology, 2017)

Erratum to: Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

SZC017, a novel oleanolic acid derivative, induces apoptosis and autophagy in human breast cancer cells - Lei Gao; Yan Wang; Zhen Xu; Xiaorui Li; Jingjun Wu; Shumin Liu; Peng Chu; Zhengwu Sun; Bin Sun; Yuan Lin; Jinyong Peng; Guozhu Han; et al. (Apoptosis, 2015)

Phosphocreatine protects endothelial cells from oxidized low-density lipoprotein-induced apoptosis by modulating the PI3K/Akt/eNOS pathway - Anil Ahsan; Guozhu Han; Junfang Pan; Shumin Liu; Arshad Ahmed Padhiar; Peng Chu; Zhengwu Sun; Zonghui Zhang; Bin Sun; Jingjun Wu; Aisha Irshad; Yuan Lin; et al. (Apoptosis, 2015)

One novel cis-element is essential for correct DYSFUNCTIONAL TAPETUM 1 (DYT1) expression in Arabidopsis thaliana - Zhou Shumin; Chen Yan; Sun Hulin; Zheng Bang; Sun Licheng; Zhang Wei (Plant Cell Reports, 2015)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Antimicrobial effect and membrane-active mechanism of tea polyphenols against Serratia marcescens - Shumin Yi; Wei Wang; Fengling Bai; Junli Zhu; Jianrong Li; Xuepeng Li; Yongxia Xu; Tong Sun; Yutang He (World Journal of Microbiology and Biotechnology, 2014)

Complex structures of transgene rearrangement implicate novel mechanisms of RNA-directed DNA methylation and convergent transcription - Zheng Liu; Shuangcheng Gao; Shumin Zhang; Shangjun Yang; Ning Sun (Genes & Genomics, 2014)

Calcium ameliorates obesity induced by high-fat diet and its potential correlation with p38 MAPK pathway - Chao Sun; Li Wang; Jun Yan; Shumin Liu (Molecular Biology Reports, 2012)